A New Modification of Adomian Decomposition Method for Solving Nonlinear Parabolic Partial Differential Equations - Huseen, Shaheed N.; Karim, Mustafa Q. (Iraqi Journal of Science, 2025)
In this article, a new modification of the Adomian decomposition method is presented for finding analytical and approximate solutions of nonlinear parabolic partial differential equations. And Comparison of obtained result with some previous methods.